APLIKASI ALJABAR PADA KRIPTOGRAFI DAN KEAMANAN INFORMASI - Zaki Riyanto, Muhamad (Jurnal Ilmiah AdMathEdu, 2011)
The confidential information that sent via an insecure communication channels like the internet, have a greater risk to be tapped by the parties are not entitled to know the confidential information. One of the things that can be done is to encrypt information into code that can not be understood. Art and science to keep the confidentiality of information is called cryptography. Historically, cryptography has been used since ancient Roman times, world war, until the digital age and information technology as it is today. From the beginning of its development, the method used for the encoding process using simple calculations. Along with the development of technology, the methods used are also growing, such as the use of computers with mathematical calculations are complicated. One area of ??Mathematics that has a very important role in cryptography is algebra. Many of the methods used in cryptography using algebraic operations are defined over an algebraic structure, as in the group, ring and field. In this paper, its discussed about several applications of algebra that used in cryptography, especially on the structure of algebra (abstract algebra) and linear algebra. Given cryptographic method is Caesar cipher, shift cipher, permutation cipher, Hill cipher, ElGamal and RSA.